Chemical composition and antioxidant activity of date palm Fruit (Phoenix dactylifera) in Saudi Arabia - Abdoh, Yousef (2018)
Dates are the fruit of the palm, which the Greeks call “Phoenix”, a word taken from the Phoenician language. Saudi Arabia is currently one of the largest dates producing countries in the world. There are several varieties of dates grown in Saudi Arabia. Date fruits contain compounds that are potentially bioactive, with many health benefits; for example, vitamin E, carotene (precursor for vitamin A) and phenolic compounds. Dates represent an excellent source of antioxidants due to their high concentrations of phenolic compounds as well as the presence of selenoproteins. Moreover, dates are also potentially a very good source of several minerals in fact; there are at least 15 minerals found in dates. The work presented in this thesis will determine the nutritional composition of nineteen varieties of dates sourced from four, environmentally diverse, regions in Saudi Arabia. These varieties were selected because of their popularity, economical price, as well as availability during the year. The results indicated that the range of moisture contents (10% - 30%) found within the four regions were quite similar. For levels of fat, protein and ash all varied significantly between varieties but were all very low. Carbohydrate content was variable between samples (70 - 80%). The results indicated that glucose and fructose concentrations in theses Saudi dates were generally similar and the present of sucrose being normally associated with a corresponding reduction in the level of glucose and fructose. Potassium was the major mineral found in all the varieties with concentrations as high as 1173.29 mg/100g. The mean values for phosphorus in the dates from the different regions were close to each other. The amount of selenium was generally very low in all varieties and some did not contain any selenium at all. It would appear that it is variety and not region of production that has the major impact on nutritional composition. Moreover, this research will also determine the antioxidant capacity and phenolic content of a sub-set of these varieties at four different stages of ripening. Results showed that the levels of phenolics, anthocyanin and antioxidant capacity all decreased throughout development in all the seven selected varieties. There were strong correlations between this antioxidant capacity and the total phenolic and anthocyanin levels suggesting that these are major contributors to this nutritional property of dates. A preliminary screen tentatively identified some phenolic compounds and indicates that there may be some compositional variation between date varieties.